PEMODELAN JUMLAH PENUMPANG PESAWAT DI BANDARA SOEKARNO-HATTA MENGGUNAKAN MODEL HYBRiD SARIMA-FTSMC - M. Pio Hidayatullah; Ferra Yanuar; Dodi Devianto (LPPM Universitas Bina Bangsa, 2023)
The aim of this research is to model the number of airplane passengers at Soelkarno-Hatta airport using a model hybrid SARIMA-FTSMC. The data used in this research is secondary data in the form of data on the number of airplane passengers at Soekarno-Hatta airport from January 2010 to May 2023 which was obtained via the websitebps.go.id. After analyzing the data, the best model was obtained in the SARIMA model, namely SARIMA(1,1,1)(0,1,1)12. Then based on the residual value from the processed data SARIMA will be modeled using the FTSMC model. Next, the residual value of SARIMA(1,1,1)(0,1,1)12 which has been modeled using the FTSMC model is added to the modeling value from SARIMA (1,1,1)(0,1,1)12 known as a modelhybrid SARIMA-FTSMC, with the aim of obtaining a higher level of accuracy or smaller error compared to the SARIMA model. After that, the accuracy level of the model is calculatedhybrid SARIMA-FTSMC uses MAD, MSE, and MAPE. In this research, the level of accuracy of the model was very good, this was shown by the MAPE value being less than 20%.